Respect: Response to shame in health care - Burton, Laurel Arthur (Journal of religion and health, 1991)
Shame is a not uncommon experience of patients in health care settings. Religious assessments often confuse shame with guilt, and therefore respond in ways that may not be appropriate. Illustrated by a case study, this article distinguishes shame from guilt and examines systemic considerations. Then shame is explored in relation to traditional, negotiating, and individualistic belief paradigms, looking at epistemology, causality, response to shame, healing models, and tasks. It concludes with a discussion of the idea of "respect" as foundational for responding to people experiencing shame in health care.